2007
DOI: 10.1002/jnr.21440
|View full text |Cite
|
Sign up to set email alerts
|

Rapid promoter analysis in developing mouse brain and genetic labeling of young neurons by doublecortin‐DsRed‐express

Abstract: Characterization of neural promoter/enhancers is essential for understanding gene regulation during brain development and provides useful genetic tools. However, it relies on the use of transgenic mice. We report a method for the rapid in vivo analysis of neural promoter/enhancers in the developing mouse brain and its application in the isolation of the doublecortin (DCX) promoter/enhancer for genetic labeling of young neurons. In the present study, we demonstrated that reporter genes introduced into the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 21 publications
3
69
0
Order By: Relevance
“…Our results showed that MACF1 deficiency results in aberrant dendrite and axonal differentiation including immature spines and insufficient dendritic branching and callosal axon innervation. The Dcx-cre-iGFP construct uses the mouse doublecortin (Dcx) promoter to drive expression of Cre recombinase in immature and young neurons [50,30]. Dcx-positive immature neurons are primarily found in the intermediate zone where undifferentiated neurons start migrating toward the pia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MACF1 deficiency results in aberrant dendrite and axonal differentiation including immature spines and insufficient dendritic branching and callosal axon innervation. The Dcx-cre-iGFP construct uses the mouse doublecortin (Dcx) promoter to drive expression of Cre recombinase in immature and young neurons [50,30]. Dcx-positive immature neurons are primarily found in the intermediate zone where undifferentiated neurons start migrating toward the pia.…”
Section: Discussionmentioning
confidence: 99%
“…Electroporated plasmids were as follows. Dcx-GFP, the minimal promoter for mouse Dcx gene (2 kb upstream genomic sequence of the Dcx gene) (Wang et al, 2007), was amplified by genomic PCR and cloned upstream to the GFP sequence from the EGFP-C1 plasmid (Clontech); pCig2-ires-GFP plasmid [CMV-enhancer/chicken ␤-actin promoter-GFP (CMV-GFP)] (kind gift from F. Polleux, The Scripps Research Institute); Dcx short-hairpin (Sh) RNA plasmid was produced from the SureSilencing ShRNA plasmid (SABiosciences Qiagen, Frederick, MD), where the following sequence, 5Ј-TCACCTGTCTCCATGATTTCT-3Ј (targeting specifically dcx mRNA), was subcloned in the pGeneClip vector downstream to the U1 promoter to express the ShRNA. For control experiments related to migration studies, the same SureSilencing ShRNA plasmid was used with a scrambled noncoding sequence (5Ј-GGAATCTCATTCGATGCATAC-3Ј) instead of the dcx sequence, and no defect was observed.…”
Section: Methodsmentioning
confidence: 99%
“…1 Math1 is specifically expressed in GNPs and frequently used as a GNP marker, 29,30 whereas Dcx is found to be expressed specifically in the early differentiated GNPs. [31][32][33] To analyze the biological function of Stox1 in postnatal cerebellar neurogenesis, we constructed a Stox1-expressing adenovirus that co-expressed tomato red fluorescent protein as a reporter. Math1-GFP and Dcx-DsRed reporter mice in which the Math1 or Dcx expressing granule neurons can be readily identified using respective fluorescent protein were introduced from the Jackson Laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Math1-GFP and Dcx-DsRed reporter mice in which the Math1 or Dcx expressing granule neurons can be readily identified using respective fluorescent protein were introduced from the Jackson Laboratory. 30,33 GNPs from day 6 Math1-GFP reporter mice were purified by percoll gradient sedimentation method, 34 plated on poly-D-lysine coated plates, and then infected with Stox1-expressing adenovirus. Stox1 overexpression was validated by quantitative RT-PCR and immunobloting (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%